PSXI-3 Impact of carbohydrate source on manure and air emissions from swine diets. (5th December 2019) - trabue, Steven; Kerr, Brian; Andersen, Daniel
Abstract: Dietary fiber is known to reduce ammonia emissions, but little is known about its effect on emissions of major odorants. An experiment was conducted to determine the effect fiber and fiber source has on manure composition and gas emissions. Two groups of 44 gilts averaging 128 kg BW were fed standard corn soybean meal diets that contained 9.6% NDF or 17% NDF with the following fiber sources: beet pulp (BP); dried distillers grain with solubles (DDGS); soybean hulls (SB); and wheat bran (WB). Animals were fed twice daily, and feces and urine were collected after each feeding and added to manure storage containers. At the end of the experiment, stored manures were monitored for gas emissions and chemical properties. Animals on average gained 724 g/d and consumed 2.74 kg feed/d over 42-d trial ANOVA showed that dietary fiber in swine diets significantly increased the animals manure acidity, dry matter (DM), organic N, total N, total C, and volatile fatty acids contents, while the source of the fiber material in the diet significantly impacted the animals manure DM, total N, total C, and total S. Manures of animals fed lower fiber diets had significantly higher ammonia (NH3 ) and hydrogen sulfide emissions, while manure emissions of NH3 and total phenols was impacted by the fiber source in the animal diet. In conclusion, dietary fiber and the source of fiber have a dramatic impact on manure composition and gas emissions.